HUBUNGAN PENGETAHUAN TENTANG PERSONAL HYGIENE DENGAN PENYEMBUHAN LUKA PERINEUM PADA IBU NIFAS DI WILAYAH KERJA PUSKESMAS SERONGGA KABUPATEN KOTABARU - Boru Nainggolan, Tiomora; Rahmawati, Dwi; Sarkiah, Sarkiah (Midwifery And Complementary Care, 2022)
Background: The perineum is an area that is not easy to care for. If perineal wound care is inadequate, it can lead to infections, which are inflammations of the entire genital area of the mother, marked by an increase in the mother’s body temperature up to 38°C. This may result in complications ranging from bladder infections to infections in the birth canal, and can even lead to maternal death. Serongga Community Health Center in Kotabaru Regency is one of the community health centers with the highest number of postpartum mothers in the region. Objective: To analyze the relationship between knowledge of personal hygiene and perineal wound healing in postpartum mothers in the working area of Serongga Community Health Center, Kotabaru Regency. Method: This research was conducted in the working area of Serongga Community Health Center, Kotabaru Regency, over a period of three days from February 23–25, 2023. It used an analytical survey method with a cross-sectional approach. Samples were taken using accidental sampling technique, involving 30 postpartum mothers with perineal wounds in the working area of Serongga Community Health Center, Kotabaru Regency. Bivariate analysis was performed using Chi-Square statistical testing. Results: Based on the research results, the majority of respondents had good knowledge, totaling 17 individuals (94.4%), with a p-value of 0.026, indicating a significant relationship between knowledge of personal hygiene and perineal wound healing in postpartum mothers. Keywords: Postpartum mother, knowledge, perineal wound care